magistyka społeczno-kulturowa w średniowiecznej Serbii, czyli o strategii budowania wizerunku serbskich panujących: Social-cultural representation in the medieval Serbia namely, on the strategies of creating the image of Serbian rulers - Lis-Wielgosz, Izabela (Przegląd Wschodnioeuropejski, 2020)
In the article, a phenomenon of promotion and marketing in the medieval Serbia was discussed, as well as the strategies of creating a specific, desired and functional image of the ruling dynasties. Due to this, the basic communication practices were recalled that is, a management of impression, building the so-called brand (social, political, cultural property of the dynasty, its family pattern), and also specifically conceived branding itself (that is, a management of consciousness and value of the dynastic brand), what ultimately proved that the lineage of social-cultural usage of images, along with the models and devices serving the politics of public relations is deeply rooted in the middle ages. The phenomenon of promotion and marketing in the medieval Serbia was presented on the basis of the medieval Serbian literature, hagiography, hymnography, historiography, and iconographic implementations were also included. The article presents images of rulers and dynasties prevailing in the historical, religious and ideological context, the phenomenon of promotion and marketing in the context of characteristic ideological structures, such as state and church tradition, imperial-monastic tradition, charismatic dynasty, sanctity of the ruling family, land and the Serbian nation e.t.c. The timeless phenomenon of promotion and marketing has been presented as a lasting component of shaping the culture model of the medieval Serbia.